Impact of employees stress on job performance in the public sector organizations: special reference to eastern province - Priyadharsan, S. (University of Jaffna, 2012)
This research is identifying the impact of employees stress on job performance in the public sector organization. Special reference to Chief Secretary Cluster of Eastern Province. Undoubtedly in every organization, a small group of the working population suffers from stress. Public sector organizations employees are normative commitment. The purpose of this study is under government scheme for recruitment of unemployed graduates, 3641 Graduates were recruited as Programme Assistants to the North East Public Service during 2005, but at presently only 638 employees are working in the Eastern province. Impact of high stress entails low organizational commitment, which directly contributes to voluntarily termination of employees and may lead to low overall firm’s performance. Objective of the research is to identify the factors influences on stress in the organization, to identify the impacts of stress on job performance, to measure the which factor is highly influence on job performance and to reduce the employee stress and enhance the job performance through various activities. Conceptual frame work included individual stress, organizational stress and environmental stress. Selected sample is 122 programme assistant based on the five years experience. The data analysis included the univariate, bivariate and multivariate analysis. The findings of the study show that all three variables have negative relationship with job performance, particularly organizational stress highly impact of job performance. As per the multiple regression analysis, 58 percent of the variance is found in the job performance. Further research found the rest of the 42 percent of the variance. Some recommendations are suggested to improve their job performance
Keywords: Job performance; Work place stress